Assessment of urban lake water quality at three different types of soil properties - Wan Syibrah Hanisah Wan Sulaiman
The assessments of water quality in Malaysia depend on several guidelines such as National Lake Water Quality Criteria and Standard, Urban Storm Water Management Manual for Malaysia and National Water Quality Index Standard. However, these guidelines are very limited in evaluating the status of water quality without considering the significant contribution that affected the quality of water, such as the type of soil. The concern of soil problems in Malaysia arising from laterite, sandy, acid sulphate and organic soil. In addition, the soil is a pollutant-transmitting agent of water run-off and enhance the toxicity level in soil and water bodies. Thus, this research aimed to confirm the interaction between the cation exchange capacity (CEC) of 3 different types of problem soil towards water quality index. The relationship between CEC and urban lake quality index was investigated and verified by spectrophotometry and ICP-MS towards soil and water physicochemical properties as well as heavy metals content. This study established that laterite, sandy and acid sulphate soil differ significantly with respect to CEC, soil texture, soil colour and distribution and concentrations of heavy metals in soil and water bodies. A total 100 samples were evaluated for quantitative and qualitative physicochemical properties in 3 different types of soil, water bodies, and heavy metals. Soil colour was found to correlate with CEC and heavy metals content in both soil and water bodies. The main heavy metals group identified in laterite soil were Fe, Al, Mn and Zn whereas in sandy and acid sulphate soil only Al and Mn were detected. The ratio of these heavy metals series varies between the type of soils. CEC value was detected higher in laterite soil (9.35 to 22.85 mg/kg) whereas in sandy and acid sulphate soil CEC were found less than 10 mg/kg. On the other hand, the main heavy metals group identified in water bodies in urban lake at laterite were Fe, Al, Mn and Zn; at sandy area were Pb, Cr, Fe, Ni, Al and Cd and water bodies at acid sulphate soil area were Mn, Al, Fe and Cr. Marked differences were observed between the heavy metals content and concentration in soil and the urban lake water bodies. Therefore, heavy metals profiles of the 3 different types of soil and water bodies showed highly significant differences between the CEC, soil colour, soil texture, and all other combinations of interactions, indicating the complex nature of factors influencing water bodies composition. Reflectance colorimeter measurement of yellow-red hue component in this study confirmed that the higher the CEC content, the greater the yellow-red intensity colour and clay content. Lastly, in order to complete this study, an effective rating system using physico-chemicals properties were established to assess urban lake quality index status based on both water bodies and specific type of soil parameters influencing heavy metals composition.